2014
DOI: 10.1186/1471-2474-15-30
|View full text |Cite
|
Sign up to set email alerts
|

Design process of cementless femoral stem using a nonlinear three dimensional finite element analysis

Abstract: BackgroundMinimal available information concerning hip morphology is the motivation for several researchers to study the difference between Asian and Western populations. Current use of a universal hip stem of variable size is not the best option for all femur types. This present study proposed a new design process of the cementless femoral stem using a three dimensional model which provided more information and accurate analysis compared to conventional methods.MethodsThis complete design cycle began with mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 53 publications
(134 reference statements)
3
7
0
1
Order By: Relevance
“…The clear distal load transfer after the implantation of both short stems demonstrated in this study is congruent with previous studies, which have found a similar distally shifting load distribution pattern as a result of implant insertion [ 24 , 61 , 62 ]. Despite the fact that short-stem femoral implants have displayed a better biomechanical behavior preserving a strain distribution closer to the intact bone according to previous studies [ 24 , 28 , 42 , 43 , 63 65 ], the implantation of a stiffer material absorbs the load and transfers it distally, leaving the proximal region of the calcar somewhat stress-shielded.…”
Section: Discussionsupporting
confidence: 92%
“…The clear distal load transfer after the implantation of both short stems demonstrated in this study is congruent with previous studies, which have found a similar distally shifting load distribution pattern as a result of implant insertion [ 24 , 61 , 62 ]. Despite the fact that short-stem femoral implants have displayed a better biomechanical behavior preserving a strain distribution closer to the intact bone according to previous studies [ 24 , 28 , 42 , 43 , 63 65 ], the implantation of a stiffer material absorbs the load and transfers it distally, leaving the proximal region of the calcar somewhat stress-shielded.…”
Section: Discussionsupporting
confidence: 92%
“…The clear distal load transfer after the implantation of both short stems demonstrated in this study is congruent with previous studies, which have found a similar distally shifting load distribution pattern as a result of implant insertion (24,61,62). Despite the fact that short stem femoral implants have displayed a better biomechanical behavior preserving a stain distribution closer to the intact bone according to previous studies (24,28,42,43,(63)(64)(65), the implantation of a stiffer material absorbs the load and transfers it distally, leaving the proximal region of the calcar somewhat stress-shielded.…”
Section: Discussionsupporting
confidence: 92%
“…However, there is no universal off shelves hip implant that suits all populations [3][4][5]. The peculiar hip morphology for the ASEAN population, especially at the neck-shaft angle, femoral head offset, isthmus location, and mediolateral region promote the development of an appropriate implant's design that complies ASEAN hip anthropometric [6][7].…”
Section: Introductionmentioning
confidence: 99%